Опыт внедрения частотно-регулируемого электропривода насосной станции аммиакопровода - Горбачев, Николай Васильевич; Хомяков, Александр Яковлевич; Розкаряка, Павел Иванович (НТУ "ХПИ", 2013)
The methodology and experience of implementing variable-frequency induction motor drive systems for the pumping station of enterprise «Ukrhimtransammiak» are summarized. The introduction permits to save energy by increasing the efficiency, to reduce the wear of the technological and electrical equipment, to improve the reliability of the operation, to increase the service life, to reduce costs of the repair and the service.
Keywords: энергосбережение; средства электропривода; энергоемкость предприятий; частотное регулирование скорости; регулирование дроссельной заслонкой; автоматизированное управление насосом